The Interplay of Stress, Health and Spirituality among migrant construction workers. - C Janarthan; Lone, Ahrar Ahmad (South Eastern European Journal of Public Health, 2025)
Stress is a ubiquitous aspect of modern life, affecting individuals across various demographics and socioeconomic backgrounds including migrant construction workers. This paper aims to explore the complex interrelationship between stress, spirituality, and overall health among migration construction worker.The author has conducted a thorough review of the relevant literature, drawing insights from a range of scholarly sources, earlier field studies and observational research conducted by author that explore the Interplay of Stress, Health and Spirituality among migration construction workers. From the above, some of the findings are highlighted here (i)Migrated construction workers experience numerous health problems due to their excessive working hours, deficiency of leisure time and recreational opportunities and stressors. Stressors include traumatic experiences, persistent pressures, and unfavourable occurrences, constituting a stressful life events,(ii) These stressful life are positively correlated with both physical and mental illnesses, according to a number of research. (iii) Proper rest and leisure is a pre-requisite to spirituality which in turn reduces the stress It is the responsibility of every relevant party, especially officials, engineers, along with supervisors who regularly have direct contact with workers for strict implementation of Right to rest and leisure and arrange for spiritual activities such as yoga and mediation in morning and evening to start with in the construction sites It is also to arrange for spiritual activities such as yoga and meditation in the labour colonies. Attitudinal change of all concerned with the construction activities with spirituality is essential.